2021
DOI: 10.1136/gpsych-2020-100448
|View full text |Cite
|
Sign up to set email alerts
|

Depression, suicidality and associated risk factors among police officers in urban Tanzania: a cross-sectional study

Abstract: BackgroundThe WHO has classified depression as a disease of public concern. Police officers are a particular subpopulation group that is at an increased risk for mental health problems. This study examined the prevalence of depression, suicidality and associated risk factors among police officers in urban Tanzania.AimsThe aim of this study was to examine the prevalence of depression, suicidality and associated risk factors among police officers in Tanzania.MethodsA cross-sectional study was conducted between A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
0
10
0
5
Order By: Relevance
“…It can come in any form, as Cohen [ 34 ] mentions, and can create a sense of belonging and even help workers overcome obstacles. A total of nine studies (45%) [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] highlighting the importance of social support from organizations were included in this review. The absence or presence of social support from organizations was assessed in a cross-sectional study using a validated scale and an ad hoc questionnaire.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It can come in any form, as Cohen [ 34 ] mentions, and can create a sense of belonging and even help workers overcome obstacles. A total of nine studies (45%) [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] highlighting the importance of social support from organizations were included in this review. The absence or presence of social support from organizations was assessed in a cross-sectional study using a validated scale and an ad hoc questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…Violanti et al [ 37 ] showed that police officers who perceived low social support showed increased PTSD symptoms and used lower levels of active coping. In addition, Njiro et al [ 38 ] found that police officers who perceived a lack of social support were at increased risk for depression and suicidality. Wray and Jarrett [ 39 ] also emphasized that limited opportunities for support can increase suicidal ideation and the risk of burnout.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these officers had communicated their suicidal intent to others. In addition, Njiro et al (2021) reported that depression and low support were intertwined in predicting suicidal ideation. A small number of police officers had a history of previous suicide attempts, with this more prevalent for women (Berg et al 2003;Di Nota et al 2020).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%